PREVALENSI BENDA ASING PADA ESOFAGUS DAN BRONKUS DI BAGIAN/SMF THT-KL FK UNUD/ RSUP SANGLAH DENPASAR TAHUN 2010-2012 - Bagus Rizky Kornia; Sari Wulan Sutanegara; Wayan Sucipta (DiscoverSys Inc., 2016)
Prevalence of foreign body objects in the esophagus and bronchus at the Department of Otolaryngology Faculty of Medicine UNUD/RSUP Sanglah Denpasar in 2010-2012.ABSTRACTMost people have little attention on the problem of foreign bodies that enter organs, patients come to the hospital or to the doctor after the foreign bodies showed serious symptoms that make patients feel uncomfortable or feel pain. The purpose of this study is to obtain the characteristics of patients with foreign body objects in the esophagus and bronchus in the Department of Otolaryngology Faculty of Medicine UNUD/RSUP Sanglah Denpasar in 2010-2012. This research is a descriptive study with cross sectional (retrospective) design.From the 56 cases obtained, the majority of patients were male (31 person, 55,4%), and based on the age group, most of the patients are under 5 years of age ( 16 person, 28,6%). Most of the foreign body that was found are categorized organic (30 case, 50,36%). Metal coin as the majority foreign body acquired (17 case, 30,4%). According to the location of obstruction, the esophagus was the most frequent location that had a foreign body with 46 cases (82,1%).Itâ€™s recommended for parents to pay attention to their children while playing with the non-organic objects like metal coin potensial in entering body carity especially esophagusÂ